Interface coupling in graphene/fluorographene heterostructure for high-performance graphene/silicon solar cells. (October 2016) - Zhong, Mengyao; Xu, Dikai; Yu, Xuegong; Huang, Kun; Liu, Xuemei; Qu, Yiming; Xu, Yang; Yang, Deren
Abstract: One-step approach for doping and interface engineering of the Gr/Si solar cells was realized by using the fluorographene(FG) as an insulator interlayer. Metal/insulator/semiconductor (MIS) like solar cells with a structure of Gr/FG/Si were composed. The F atoms of FG serve as electron acceptors and yield p-type doping, which is beneficial for improving the Schottky barrier. The carrier recombination of the solar cell can be effectively suppressed by the employment of the FG interlayer and the PCE of the solar cell increased from 3.17% to 7.52%. More interestingly, the performance of Gr/FG/Si solar cell can be further enhanced by applying a temporary voltage bias, which was likely associated with rotation of the C―F bonds or/and enhancement of the Gr/FG coupling in electrical field. A PCE up to 13.38% was achieved by combining the AR technology and chemical doping from the top-side of the Gr. Graphical abstract: Highlights: We fabricated metal/insulator/semiconductor (MIS) solar cells with a structure of Gr/FG/Si. Underside p-type Gr doping was obtained in the Gr/FG heterostructure. One-step approach for doping and interface engineering of the Gr/Si solar cells was realized. Performance of Gr/FG/Si solar cell was further enhanced by applying a temporary voltage bias. PCE of 7.52% and 13.38% were achieved for the pristine Gr/FG/Si solar cell and after AR technique and chemical doping.